Preliminary research on protective functional mapping for a basin base on ecological landscape analysis and assessment applied at Chu River basin, Thanh Hoa province - Vinh, Pham The; Thinh, Vo; Tu, Nguyen Huu; Tai, Vu Anh (Vietnam Journal of Earth Sciences, 2014)
This paper presents preliminary result of a method to analysis and assessment of landscape to aim protective functional mapping for a basin as a sample as Chu River in Thanh Hoa province. Base on the ecological landscape map at scale of 1 : 100 000 that includes 1 system, 1 sub-system, 3 classes, 10 types, 26 ranks and 397 series of ecological landscape units we select indicators to response for protective function levels of the basin that includes slope degree, soil thickness, soil mechanic elements, elevation, rainfall, length of rain season, length of cold season, degree of forest canopy to assess the characters of landscape elements that would affect on hydrological control of landscape type. The analysis results to 6 levels of protective function: very importance, importance, nearly importance, non importance, safety and completed safety; those levels also combine with 10 landscape types. It also results to complete a map of protective functional levels base on levels of ecological landscape units within Chu River Basin at scale of 1:100.000.